Eksplorasi Strategi Preventive Maintenance dan Tantangan Penerapan Overall Equipment Effectiveness pada Armada Truk PT Karya Indah Multiguna - Yesayas Juleith Anggi; Ari Setiawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study explores the preventive maintenance strategies and the challenges in implementing Overall Equipment Effectiveness (OEE) in managing the logistics truck fleet at PT KIM. The primary objective of this study is to gain an in-depth understanding of how preventive maintenance strategies are carried out within the company and to what extent the application of the OEE concept supports operational efficiency. Utilizing a qualitative approach and case study method, the research reveals that although PT KIM has implemented various preventive maintenance procedures, their effectiveness is still hindered by factors such as limited driver involvement, the absence of a reward and punishment system, and the lack of integration in reporting systems across departments. Moreover, the implementation of OEE has not been optimal due to low data integration and the use of manual reporting systems, which lead to delays in information flow and ineffective decision-making. An analysis based on the Total Productive Maintenance (TPM) theory highlights that weaknesses in administrative aspects (TPM in office) serve as a major obstacle to improving fleet performance effectiveness. The findings underscore the importance of a holistic and digitally integrated maintenance management approach as a foundation for enhancing the company’s logistics productivity and competitiveness. Therefore, it is recommended to strengthen technology-based reporting systems, implement cross-functional training, and cultivate an organizational culture that supports collaboration within the TPM framework.